THE IMPLEMENTATION OF COOPERATIVE AND COLLABORATIVE LEARNING APPROACHES IN IMPROVING STUDENTS’ SPEAKING SKILLS ON DESCRIBING PEOPLE MATERIAL - Nur Faidatun Rojennah (Journal Educational of Indonesia Language, 2026)
This study aims to describe the implementation of cooperative and collaborative learning approaches in improving students’ speaking skills on describing people material with the topic of athletes among tenth-grade students of SMA Zainal Abidin. This research employed a descriptive qualitative approach involving 15 female students as the research participants. The data were collected through classroom observations, field notes, speaking observation checklists, and video documentation. The learning process was conducted in three meetings through group discussions, guessing games, collaborative questioning activities, and oral presentations. The findings revealed gradual improvement in students’ participation and speaking skills. The percentage of students’ participation increased from 40% in the first meeting to 67% in the second meeting and reached 87% in the third meeting. In addition, students demonstrated improvement in vocabulary, fluency, pronunciation, and confidence. The findings indicate that the integration of cooperative and collaborative learning approaches successfully created more active, interactive, communicative, and student-centered speaking instruction. These approaches also helped reduce students’ speaking anxiety and improved social interaction among students.